Nutrient Profiling and In-Vitro Fermentation Dynamics of Maize, Bajra, Soybean Meal, and CoFS-31 Fodder used in Stall-Fed Sheep Systems - Pavan; Dombar, Ravindra; Giridhar, K S; Rathod, Prakashkumar; Prasad, Chikkagoudara Kotresh; Maroor, Abhishek (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Efficient lamb production relies on balanced rations using local feed resources. The present study evaluated the proximate composition, fibre fractions, and in-vitro metabolizable energy (ME) using standard laboratory protocols for commonly used feed ingredients such as maize, bajra, soybean meal (SBM), and CoFS-31 fodder used in stall-fed sheep production systems in northern Karnataka. Crude protein (CP) varied widely from 4.10% in CoFS-31 to 46.06% in SBM. Maize and bajra showed comparable CP contents (8.29% and 8.33%) and low crude fibre (2.21-2.29%), indicating their high energy potential. Gas production increased with incubation time in all samples, showing a rapid rise between 4 to 12 h and stabilizing thereafter. Net gas production (mL/g DM) was higher for maize (324.95), followed by bajra (311.55), SBM (243.05), and CoFS-31 (152.10). Corresponding ME values (MJ/kg DM) were 12.62, 12.22, 12.34, and 7.19, respectively. SBM recorded the higher digestibility (IVDMD 73.08%; IVOMD 79.33%), while CoFS-31 exhibited high fibre (NDF 59.73%) and lower ME, confirming its role as structural roughage. Overall, maize and bajra are rich in fermentable carbohydrates, SBM is an excellent protein source, and CoFS-31 provides essential fibre. A balanced combination of these feeds offers a region-specific, economical, and nutritionally efficient ration to enhance sheep productivity in northern Karnataka.